Photorespiration plays an important role in the regulation of photosynthetic electron flow under fluctuating light in tobacco plants grown under full sunlight - Huang, Wei; Hu, Hong; Zhang, Shi-Bao (Frontiers in Plant Science, 2015)
Plants usually experience dynamic fluctuations of light intensities under natural conditions. However, the responses of mesophyll conductance, CO2 assimilation, and photorespiration to light fluctuation are not well understood. To address this question, we measured photosynthetic parameters of gas exchange and chlorophyll fluorescence in tobacco leaves at 2-min intervals while irradiance levels alternated between 100 and 1200 μmol photons m-2 s-1. Compared with leaves exposed to a constant light of 1200 μmol photons m-2 s-1, both stomatal and mesophyll conductances were significantly restricted in leaves treated with fluctuating light condition. Meanwhile, CO2 assimilation rate and electron flow devoted to RuBP carboxylation at 1200 μmol photons m-2 s-1 under fluctuating light were limited by the low chloroplast CO2 concentration. Analysis based on the C3 photosynthesis model indicated that, at 1200 μmol photons m-2 s-1 under fluctuating light, the CO2 assimilation rate was limited by RuBP carboxylation. Electron flow devoted to RuBP oxygenation at 1200 μmol photons m-2 s-1 under fluctuating light remained at nearly the maximum level throughout the experimental period. We conclude that fluctuating light restricts CO2 assimilation by decreasing both stomatal and mesophyll conductances. Under such conditions, photorespiration plays an important role in the regulation of photosynthetic electron flow.